Building Creativity Student Through Portopolio Model Based Learning Subject Civic Education - Kurniawan, Agung (Penerbit STKIP PGRI Bangkalan, 2018)
The use of the learning model portfolio more emphasis on creative problem solving and critical thinking skills in the learning process, and provide a huge diversity of learning resources so as to increase the participation and creativity of students. Basically learning model of this portfolio is creative that allows students to practice combines the concept of the teacher's explanation or books, giving the opportunity mahaiswa to seek information outside the classroom (direct object, TV, radio, and the person/expert), create an alternative to address the topic/object covered, make a decision with regard to the concept, and formulate the steps to be done to overcome tresearch problem done using action research (classroom action research